2002
DOI: 10.1643/0045-8511(2002)002[0836:ftasai]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Freeze Tolerance and Supercooling Ability in the Italian Wall Lizard, Podarcis sicula, Introduced to Long Island, New York

Abstract: Some insular lizards show a high degree of differentiation from their conspecific mainland populations, like Licosa island lizards, which are described as affected by Reversed Island Syndrome (RIS). In previous works, we demonstrated that some traits of RIS, as melani-zation, depend on a differential expression of gene encoding melanocortin receptors. To better understand the basis of syndrome, and providing raw data for future investigations, we generate the first de novo transcriptome of the Italian wall liz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 10 publications
0
28
0
Order By: Relevance
“…R. ridibunda and probably other species listed in Table 3 correspond to this definition. However, important variation could occur within this group between amphibians and reptiles: indeed, recent studies showed that Podarcis sp die if ice content goes beyond 20% of body fluids (Claussen et al, '90;Burke et al, 2002) while R. ridibunda survive to 55% of ice (this study). Further studies focused on the physiological mechanisms occurring (or not) in response to freezing in these animals are needed.…”
Section: Discussionmentioning
confidence: 53%
“…R. ridibunda and probably other species listed in Table 3 correspond to this definition. However, important variation could occur within this group between amphibians and reptiles: indeed, recent studies showed that Podarcis sp die if ice content goes beyond 20% of body fluids (Claussen et al, '90;Burke et al, 2002) while R. ridibunda survive to 55% of ice (this study). Further studies focused on the physiological mechanisms occurring (or not) in response to freezing in these animals are needed.…”
Section: Discussionmentioning
confidence: 53%
“…The sand lizard L. agilis and the wall lizards Podarcis sicula and Podarcis muralis are not able to survive even for short periods (30 to 120 min) when kept below À1.11C and never tolerated more than 28% of their body fluid converted into ice (Weigmann, '29;Claussen et al, '90;Burke et al, 2002).…”
Section: Y Voituron Et Almentioning
confidence: 99%
“…There are a few species of reptiles, however, known to have various degrees of freeze tolerance. Some of them, e.g., the wall lizards, Podarcis muralis and P. sicula, and the boreal adder, Vipera berus, only tolerate conversion of a limited proportion of their body fluid into ice for a very brief period (less than 30% for less than 4h) (Claussen et al, '90;Andersson and Johansson, 2001;Burke et al, 2002). Others, such as the European common lizard Lacerta vivipara, the common garter snake Thamnophis sirtalis, the painted turtle Chrysemys picta, and the box turtles Terrapene carolina and T. ornata, are able to survive freezing for 24 hours and more with 30-50% of body fluids converted into ice (Storey et al, '88;Costanzo and Lee, '88;Costanzo and Claussen, '90;Costanzo et al, '95;Voituron et al, 2002a).…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic activity under freezing conditions, even if very low, is still present. It would seem important now to conduct similar experiments on highly freeze-tolerant vertebrates such as Rana sylvatica, which can endure several weeks of freezing (27), and also poorly freezetolerant vertebrates such as Podarcis sicula (4). Such comparison between animals exhibiting different levels of freeze tolerance could provide deeper insight into the evolutionary physiology of temperate ectothermic species.…”
Section: Perspectivesmentioning
confidence: 99%